2011
DOI: 10.1002/jobm.201000303
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Caenorhabditis elegans infection model for Vibrio alginolyticus

Abstract: Vibrio alginolyticus, a common bacterium in the marine environment, is a threat to marine animals and humans by causing serious infections. The present study reveals the establishment of a Caenorhabditis elegans infection model for Vibrio alginolyticus. The infection and colonization was localized in the animal by tagging V. alginolyticus with GFP and using Confocal Laser Scanning Microscopy. Chemotactic response of C. elegans to V. alginolyticus, pharyngeal distention and blockage of vulval region leading to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…XBP‐1, a transcription factor involved in the UPR is reported for its role in C. elegans larval development against P. aeruginosa infection by protecting C. elegans against ER stress generated by the innate immune system . V. alginolyticus infection initiates an immune response in C. elegans and we hypothesize the expression of PDI‐2 to be correlated with XBP‐1 in protecting C. elegans against the ER stress and to maintain cellular homeostasis. Evidence for the role of Fenneropenaeus chinensis PDI genes in innate immune response against V. anguillaram was elucidated recently .…”
Section: Discussionmentioning
confidence: 83%
“…XBP‐1, a transcription factor involved in the UPR is reported for its role in C. elegans larval development against P. aeruginosa infection by protecting C. elegans against ER stress generated by the innate immune system . V. alginolyticus infection initiates an immune response in C. elegans and we hypothesize the expression of PDI‐2 to be correlated with XBP‐1 in protecting C. elegans against the ER stress and to maintain cellular homeostasis. Evidence for the role of Fenneropenaeus chinensis PDI genes in innate immune response against V. anguillaram was elucidated recently .…”
Section: Discussionmentioning
confidence: 83%
“…In a recent study, it was proved that worms show no chemotaxis towards ethanol (Patananan et al 2015). Our group has previously reported that C. elegans avoid Vibrio alginolyticus (Durai et al 2011) whereas it gets attracted to Cronobacter sakazakii (Sivamaruthi et al 2011), which may be by the alteration of serotonin transporter (Sivamaruthi et al 2015a). When nematodes where exposed to UV-A, there was no significant change in the rate of chemotaxis behavior (data not shown).…”
Section: Discussionmentioning
confidence: 84%
“…The intensity profile of GFP was read using the Zen software provided with the microscope (Durai et al 2011). …”
Section: Confocal Microscopymentioning
confidence: 99%
“…causing gastrointestinal tract infections. However, due to ethic complaints, Dictystelium discoideum (soil-living amoeba) or Caenorhabditis elegans (nematode), have been selected for V. cholerae and V. alginolyticus infection models [3,18]. In this work, Galleria mellonella caterpillars were used to investigate the virulence of V. cholerae by comparing the wild type and an indole negative mutant.…”
Section: Effect Of Indole On V Cholerae Virulencementioning
confidence: 99%